Study Experimental Distance to Pressure Coefficient Double Cylinders Positioned Alined - Ketut Astawa; Sukadana -; Karnata - (Jurnal Energi Dan Manufaktur, 2009)
Factors affecting of coefficient of pressure are fluid velocity, fluid density, fluid viscosity and geometry of surface which is pasted by fluid. This research is conducted by variation of some factors affecting value of pressure coefficient that are surface geometry including cylindrical shape and bluff body, and variation of free stream. The pressure to be measured is based by change of oil column length (r, mm) at incline manometer which is connected to pressure tap located on cylindrical surface. Pressure data collected based on three types of space tube variation, there are 1.2D, 1.7D, and 2.2D, and three types of cylindrical diameter variation there are 2”, 2.5” and 3”, and free stream is kept to be constant at 6 m/s. The results of research show that, the higher space tube affecting on the value and position of maximum pressure on the back cylindrical. Value and position of separation point is more to be back direction as increasing of free stream. Pressure drop happen on back cylindrical at high free stream.